ALONSO DE MONTREAL (1583): EL DIBUJO DE UN RETABLO DE 1560 - Muñoz Clares, Manuel (Imafronte, 1989)
From an altarpiece design by the painter Alonso the Montreal, dated in 1560, we outline an nitroducing stutdy on this master’s biography and artistic trajectory. He carried out his work in Murcia, during the second third of the XVIth century. Through such a drawing, and due to the scarcity of this sort of examples preserved up to date, we may skerch a panoramic view of the sixteenth-century retable in Murcia, since very few specimens still remain. The contract beside the design serves us to detect, at least, the channels and torms through which sume of these works were governed in particular when they were made for private people, like in this case.